(untitled) (ASEAN Engineering Journal, 2025)
This study explores the feasibility and benefits of using a mix of 70% concrete broken chips and 30% salvage materials for subbase construction in Bangladesh, offering an innovative alternative to exclusively using virgin resources. Key findings include the salvage materials mix-design achieving lower Los Angeles Abrasion values and higher California Bearing Ratio than virgin materials, indicating superior durability and strength. Additionally, optimal compaction characteristics were observed, with higher maximum dry density and lower optimum moisture content, contributing to environmental sustainability through reduced water consumption. The mix-design's compliance with required gradation standards post-compaction and favorable pavement performance in terms of vertical displacement and shear stress, as per KENPAVE simulations, further validates its effectiveness. This research underscores the potential of incorporating salvaged materials in pavement construction, aligning with sustainable development goals and demonstrating cost-efficiency and reduced landfill usage, while maintaining industry standards.